SELECTION OF VARIETIES OF VEGETABLE CROPS FOR DRYING - D.Z.Karimova; U.I.Akramov (Journals Park Publishing, 2022)
The most important tasks for providing nutrition to the population consist in expanding the range of products, updating the composition of diets and enriching it with products of increased nutritional value and preventive orientation.
Keywords: increased nutritional value, range of products, updating the composition